WASTEWATER QUALITY MONITORING. CASE STUDY: CLUJ-NAPOCA - VÂTCA, Călin Daniel; MARTONOȘ, Ildiko Melinda; MIHĂIESCU, Radu (Studia Universitatis Babeș-Bolyai Ambientum, 2017)
In Romania, the critical situation of the wastewater treatment plants is caused by the old sewage networks and the purification installations, the modification of the sewage capacity without its adaptation to the constructive parameters, the poor managerial capacity and the poor financial situation of the public utility operators. The wastewater treatment plant from Cluj-Napoca, was recently upgraded, the technology was innovated and introduced the tertiary wastewater treatment stage. This unit collects and treats the wastewater from the city of Cluj-Napoca and from the adjacent areas. To evaluate the quality of the wastewater and of the treated water, the samples were collected over a period of 8 months (September 2015 - April 2016), daily, at the entrance and exit point from the treatment plant. Because our focus was mainly on the tertiary stage, the analyzed parameters were: pH, COD(Cr), BOD5, total suspensions, ammonium, nitrates, total N, total P. With regard to the quality of the analyzed waters, it can be concluded that all of the eight analyzed parameters show high values in the wastewater and after purification the values decrease, within the maximum permissible limits given by law.In the months with higher temperatures the quality of the wastewater is weaker, and we noticed that the monitored parameters are slightly higher but also the amount of wastewater increases. On the basis of the results we can say that the efficiency of the purification processes is very good and the tertiary stage introduced in the wastewater treatment process is of high importance especially in the reduction of the phosphorus content.